Penerapan Senam Hipertensi Sebagai Upaya Menurunkan Tekanan Darah Pada Penderita Hipertensi - Safaat, Adang; Metasari, Des; Hasmeda, Merry; Vitaloka, Sartika; Cassanova, Wilda Firsty; Marini, Yoeliet; Rohani, Tuti; Azissah, Danur (Universitas Dehasen Bengkulu, 2025)
Hypertension is one of the common health problems experienced by the community, especially the elderly, due to a lack of knowledge about the prevention and management of blood pressure. To address this issue, a community service program was implemented in the form of hypertension exercise, aiming to raise awareness and improve the residents' ability to manage blood pressure independently. This program included education on hypertension and training on hypertension exercises using methods such as lectures, discussions, and demonstrations. Participants were guided to practice exercise movements specifically designed to help lower blood pressure. Additionally, blood pressure measurements were conducted before and after the exercise to evaluate its effectiveness.The results showed an increase in residents' knowledge about hypertension and a decrease in blood pressure among participants. This demonstrates that hypertension exercise can be an effective and practical non-pharmacological solution to help the community, especially the elderly, maintain cardiovascular health. This program is expected to encourage the community to adopt regular exercise as part of a healthy lifestyle.